Evaluating Market Structure, Firm Behavior, And Sustainability In The Maritime Industry Using Scp Framework - Hesti Ekawati; Muhammad Zilal Hamzah; Eleonora Sofilda; Ahmad Ahmad (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
The maritime industry plays a critical role in global trade but faces growing pressure to integrate environmental sustainability into its operations. This research analyzes the industry using the Structure-Conduct-Performance (SCP) framework to understand the relationship between market structure, firm behavior, and both economic and environmental performance. The study provides original value by extending the traditional SCP model to include environmental sustainability, addressing a critical gap in previous research. Key research questions include how market concentration, regulatory compliance, corporate environmental responsibility (CER), and technological innovation affect both profitability and sustainability. Using qualitative data from industry professionals and maritime educators, the analysis highlights that proactive regulatory compliance and high CER commitment drive superior economic and environmental outcomes. Firms that invest in green technologies enjoy enhanced performance, while those prioritizing short-term profits struggle with long-term competitiveness. The results offer practical insights for policymakers and industry leaders, emphasizing the need for inclusive market structures and stronger regulatory frameworks to support sustainability across the sector.